Competition Policies in Emerging Economies Lessons and Challenges from Central America and Mexico - Schatan, Claudia; Rivera Urrutia, Eugenio; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Do small developing economies, or SDEs, need a specific competition policy to create competitive markets? Against the backdrop of globalization, protectionist policies that promote state ownership and heavy regulation of key industries are proving increasingly ineffective for driving growth. Countries around the world are instituting reforms to promote competition and business creation, yet the economic and political concentration of power, feeble judicial systems, and the scarcity of human and financial resources pose special challenges to SDEs. Competition Policies in Emerging Economies features an in-depth analysis of two strategic industries—telecommunications and banking—in several Central American nations which sheds light on the dynamics of the transition to deregulation and trade liberalization. Examining the lessons learned from these experiences and presenting discussion of political, legal, economic, financial, cultural, and organizational issues, the book provides unique perspectives on competition policy and economic development. Competition Policies in Emerging Economies is primarily intended for decision-makers and policy analysts in international trade and economics, and will also appeal to researchers, academics, students, and professionals in the fields of institutional and development economics, international trade, and international affairs.
Markets in Central America and Mexico: What Is Happening with Competition? -- Models of Privatization and Development of Competition in Telecommunications in Central America and Mexico -- Competition and Regulation in the Banking Systems of Central America and Mexico: A Comparative Study -- Advantages and Limitations of Costa Rica's Experience in Competition Policy. A Benchmark for the Rest of the Countries of the Central American Region -- Banking Competition in Mexico -- Findings in an International Perspective.
Keywords: Economic policy; International economics; Development economics; Economic Policy; International Economics; Development Economics